2019
DOI: 10.1016/j.cell.2019.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Ligand Modulation of a Mammalian Voltage-Gated Ca2+ Channel

Abstract: The L-type voltage-gated Ca 2+ (Ca v ) channels are modulated by various compounds exemplified by 1,4-dihydropyridines (DHP), benzothiazepines (BTZ), and phenylalkylamines (PAA), many of which have been used for characterizing channel properties and for treatment of hypertension and other disorders. Here, we report the cryoelectron microscopy (cryo-EM) structures of Ca v 1.1 in complex with archetypal antagonistic drugs, nifedipine, diltiazem, and verapamil, at resolutions of 2.9 Å , 3.0 Å , and 2.7 Å , respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
207
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 207 publications
(217 citation statements)
references
References 100 publications
(131 reference statements)
10
207
0
Order By: Relevance
“…Our data coincide with the conception of [43] on calcium channel agonists and antagonist. Identical accommodation sites for nifedipine and Bay K8644 were postulated [43]. However, if the concentration of DHP agonists is high enough to overcome the energetic barrier, the dissociation of agonistic ligands and inactivated channel would be prevented; in that case, the agonists could function as antagonists [43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data coincide with the conception of [43] on calcium channel agonists and antagonist. Identical accommodation sites for nifedipine and Bay K8644 were postulated [43]. However, if the concentration of DHP agonists is high enough to overcome the energetic barrier, the dissociation of agonistic ligands and inactivated channel would be prevented; in that case, the agonists could function as antagonists [43].…”
Section: Discussionsupporting
confidence: 90%
“…It is further planned to use cardiomyocyte cell cultures and/or cardiac tissues for elucidating the mode of action of compound 4, because it has been shown that the characteristics of the DHP derivatives, the tissue properties, and the types of stimuli are all relevant to the calcium channel modulation [42]. Our data coincide with the conception of [43] on calcium channel agonists and antagonist. Identical accommodation sites for nifedipine and Bay K8644 were postulated [43].…”
Section: Discussionsupporting
confidence: 66%
“…The two structures will hereafter be referred to as Nav1.5T and Nav1.5Q for complexes with TTX and quinidine, respectively. Unlike Cav1.1 and Cav3.1, which undergo main chain shift of the pore-forming S6 segments when binding to pore blockers such as diltiazem, verapamil, and Z944 (22,23), the two structures of Nav1.5 remain nearly identical the root-mean-square deviation (RMSD) of 0.16 Å over 771 Cα atoms ( Figure 2A).…”
Section: Pore Blockade By Quinidinementioning
confidence: 99%
“…Recently cryo-EM structures of rabbit DHPR have been determined at near-atomic resolution Zhao et al 2019). All five subunits were resolved and the molecular structure was well understood.…”
Section: Perspectives: Toward Understanding the Mechanism Of Dicrmentioning
confidence: 99%